(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The proliferation of big data has necessitated the development of advanced techniques to process and analyze data in real-time. Traditional data processing methods are often insufficient to handle the vast volumes, velocity, and variety of big data. Leveraging artificial intelligence (AI) offers promising solutions to enhance the efficiency and effectiveness of real-time big data processing and analytics. AI techniques, such as machine learning, neural networks, and natural language processing, can significantly improve data handling, storage, retrieval, and interpretation. In this paper, we explore the integration of AI into big data processing frameworks, emphasizing the benefits and challenges associated with this approach. We examine various AI models and algorithms that can be employed to optimize real-time data analytics. By analyzing recent advancements and case studies, we highlight the transformative potential of AI in managing big data within databases. Our findings indicate that AI not only accelerates data processing speeds but also enhances the accuracy and insights derived from large datasets. The paper concludes with recommendations for future research and practical implementations, underscoring the critical role of AI in the evolution of big data analytics.